Thoracoscopy assisted pulmonary lobectomy. - Walker, W. S. (1993)
BACKGROUND--This report describes a preliminary experience with six patients undergoing video imaged thoracoscopic pulmonary lobectomy. METHODS--Three left upper lobectomies, and one each of right upper, right lower and left lower lobectomy were undertaken. The resections were performed as orthodox dissectional lobectomy procedures but were carried out under videothoracoscopic imaging with instruments introduced through two stab incisions. The entire resected lobe was delivered through a 7 cm submammary intercostal incision. RESULTS--There were no operative deaths or complications attributable to the technique. In three other patients conversion to an open thoracotomy was required because of bleeding (two cases) or obscure anatomy (one case). Post-operative pain in those undergoing thoracoscopic resection was less than that encountered with standard thoracotomy and early clinic review showed the patients to be pain free with excellent shoulder movement. CONCLUSIONS--Major pulmonary resection according to standard cancer practices is feasible with videothoracoscopic techniques. This approach is likely to offer considerable functional benefit to patients. Specimen delivery through the submammary incision imposes a 5 cm primary lesion size limitation. Detailed mediastinal assessment is necessary to exclude N2 status before undertaking thoracoscopic surgery.